Characterisation and energy storage performance of 3D printed-photocurable resin/microencapsulated phase change material composite - Er, Yusuf; Guler, Onur; Ustaoglu, Abid; Hekimoglu, Gokhan; Sari, Ahmet; Subasi, Serkan; Marasli, Muhammed (Elsevier, 2024)
The 3D fabrication of microencapsulated phase change material (MEPCM) doped resin polymer composites enables the creation of complex shapes and customized designs, opening doors for many applications in fields. This investigation fabricated a range of resin/MEPCM (20 %, 30 %, and 40 % by volume) composites using a mechanical mixing technique. This study investigates how the addition of MEPCM impacts resin matrix composite's mechanical strength, latent heat storage characteristics, and ability to regulate temperature effectively. With a 40 % MEPCM additive ratio, a pure resin porosity value of approximately 0.4 % increased to around 17 %. Thanks to the production of homogeneously dispersed MEPCM added resins with production with stereolithography (SLA), 40 % MEPCM additive enabled characteristic FTIR peaks of both MEPCM and resin to appear and, melting and solidification enthalpy values reached 87.15 j/g and 86.25 j/g, respectively. MEPCM addition enhanced the thermoregulatory properties of resin by absorbing or releasing heat during temperature fluctuations. On hotter days, 8 mm-thick composites create temperature differences exceeding 11 C, while this difference exceeds 6 C in the room center case. The produced 3D printed MEPCM/resin composite can be a potential material to effectively regulate the temperature of electronic devices, food packets, building materials, and electronic devices and automotive components.
Keywords: Stereolithography; Photocurable resin; 3D Printing; Microencapsulated phase change material; Thermal energy storage